2019
DOI: 10.1016/j.vetmic.2019.108462
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking the passage of avian influenza viruses through the gastrointestinal tract of chickens

Abstract: In contrast to human influenza viruses that replicate in the respiratory tract and are airborne transmitted, avian viruses also replicate in gut epithelial cells and are transmitted via the fecal-oral route. On this route, the virus is exposed to destructive fluids of the digestive tract, which are acidic and contain the proteases pepsin (gizzard) or chymotrypsin and trypsin (intestine). Only the latter enzyme activates virus by cleaving hemagglutinin (HA) into HA 1 and HA 2 subunits.We mimicked the passage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…S protein contains two functional domains: a receptor binding domain (RBD) [2], and a second domain which contains sequences that mediate fusion of viral and cell membranes [3][4][5][6][7]. Recently, it was reported that S protein contains a potential cleavage site for furin protease [8], including four residues (Pro681 (P681), Arg682 (R682), Arg683 (R683) and Ala684 (A684)) [9][10][11][12][13]. Functionally, R682, R683, A684 and Arg685 (R685) constitute the minimal polybasic furin cleavage cite (FCS), i.e., RXYR, where X or Y is to be a positively charged arginine or lysine.…”
Section: Introductionmentioning
confidence: 99%
“…S protein contains two functional domains: a receptor binding domain (RBD) [2], and a second domain which contains sequences that mediate fusion of viral and cell membranes [3][4][5][6][7]. Recently, it was reported that S protein contains a potential cleavage site for furin protease [8], including four residues (Pro681 (P681), Arg682 (R682), Arg683 (R683) and Ala684 (A684)) [9][10][11][12][13]. Functionally, R682, R683, A684 and Arg685 (R685) constitute the minimal polybasic furin cleavage cite (FCS), i.e., RXYR, where X or Y is to be a positively charged arginine or lysine.…”
Section: Introductionmentioning
confidence: 99%
“…The major force guiding the evolution of AIVs is the adjustment with new hosts or the escape from the pre-existing host community [31]. This process of evolution is assisted by nucleotide substitutions involving amino acid mutations and reassortments [32].…”
Section: Discussionmentioning
confidence: 99%
“…In the appropriate conditions, AIV can remain infective for up to 6 months in surface waters ( Keeler et al, 2014 ). AIV are rapidly inactivated by low pH and bile acids ( Hirose et al, 2016 ; Scholtissek, 1985 ); although, evidence has shown that mucus can provide protection from inactivation in the gastrointestinal environment ( Hirose et al, 2016 ), and the possibility of water being a diluent to lower the pH of the stomach and allow AVI to pass has also been suggested ( Han et al, 2019 ).…”
Section: Avian Influenza Virusesmentioning
confidence: 99%
“…There is growing evidence that specific enveloped respiratory viruses can endure low pH, enzymes, and bile in the upper GI tract and replicate in the intestinal epithelium ( Bertran and Swayne, 2014 ; de Wit et al, 2014 ; Zhou et al, 2017 ). The potential deleterious effect of low pH and digestive enzymes on viruses can also be mitigated if viruses are swallowed with water or food ( Han et al, 2019 ). Food and water can also decrease the activity of pepsin, which could otherwise degrade virus particles ( Witkowski et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%